Hak-Hak Pekerja Rumah Tangga dan Perlindungan Hukum di Indonesia - Muhammad Yafi Azhari; Abdul Halim (Universitas Airlangga, 2021)
The purpose of this study is to analyze the rights of informal domestic workers and legal protection in Indonesia through Law Number 13 of 2003 concerning Manpower and Regulation of the Minister of Manpower (Permenaker) Number 2 of 2015 concerning Protection of Domestic Workers. This type of research is qualitative using a normative-empirical approach. Sources of data include primary data in the form of interviews, while secondary data through statutory approaches and document studies. The results show that the rights of domestic workers have not been fully regulated to provide a decent life for domestic workers and the drafting of Permenaker No.2 of 2015 has not become a state protection for domestic workers because the regulation focuses on supervising channeling agencies. Therefore, government awareness of the existence of domestic workers is necessary.Keywords: Domestic workers; Legal protection; Regulation.Tujuan dari penelitian ini untuk menganalisis hak-hak pekerja rumah tangga informal dan perlindungan hukum di Indonesia melalui Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan dan Peraturan Menteri Ketenagakerjaan (Permenaker) Nomor 2 Tahun 2015 tentang Perlindungan Pekerja Rumah Tangga. Jenis penelitian ini kualitatif dengan menggunakan pendekatan normatif-empiris. Sumber data meliputi data primer berupa wawancara sedangkan data sekunder melalui pendekatan ilmu perundang-undangan dan studi dokumen. Hasil menunjukan bahwa hak pekerja rumah tangga belum diatur secara lengkap untuk memberi kehidupan yang layak bagi PRT dan pembuatan Permenaker Nomor 2 Tahun 2015 belum menjadi perlindungan negara kepada pekerja rumah tangga karena peraturan tersebut berfokus untuk mengawasi lembaga penyalur. Kata Kunci: Pekerja Rumah Tangga; Perlindungan Hukum; Pengaturan.